A new name for Epigeneium arunachalense A.N.Rao (Orchidaceae) - Verma, Durgesh; Barbhuiya, Hussain Ahmed (Phytotaxa, 2014)
Molecular and morpho-taxonomic studies (Schuiteman 2011, Xiang 2013, Schuiteman 2014) have established that the genus Epigeneium Gagnepain (1932: 593) forms a clade with the genus Dendrobium Swartz (1799: 82) and in view of the minor genetic and morphological differences it has been merged with the latter. Most of the names treated under Epigeneium have combinations in Dendrobium already. However, Epigeneium arunachalense Rao (2010: 3) has not yet been transferred to Dendrobium. The existence of the previously published Dendrobium arunachalense Deori, Sarma, Phukan & Mao (2006: 81) raises the need of a new name for the species.